Obstetric Anal Sphincter Injuries (OASIS) in Multiparous Women With the Use of Epidural Anaesthesia: A Retrospective Cohort Study. Issue 4 (December 2021) - Putri,; Simons, K.; Nettle, J.; Woodward, A.
Abstract : ( Aust N Z J Obstet Gynaecol . 2021;61:30–34) Epidural anesthesia is the gold standard for managing labor pain. But it is also associated with longer second stage of labor and an increased risk of instrumental vaginal delivery, which can lead to obstetric anal sphincter injuries (OASIS). The risk of OASIS is 5.7% in women giving birth for the first time, compared with 1.5% in multiparous women with no history of OASIS. The aim of this study was to evaluate the impact of epidural use in multiparous women on the rates of OASIS and other outcomes.